Estimating catastrophic costs due to Pulmonary Tuberculosis in Bangladesh - Chowdhury, Anita Sharif; Ahmed, Md Shakil; Ahmed, Sayem; Khanam, Fouzia; Farjana, Fariha; Reza, Saifur; Islam, Shayla; Islam, Akramul; Khan, Jahangir A.M.; Rahman, Mahfuzar (Atlantis Press, 2022)
This article was published in The Journal of Epidemiology and Global Health [©2020 Published by Atlantis Press, part of Springer Nature and Open access, licensed under CC BY-NC-ND 4.0] and the definite version is available at: https://doi.org/10.2991/jegh.k.200530.001 The Article's website is at: https://www.atlantis-press.com/journals/jegh/125941081